49.0k views
1 vote
Solve for x


-5(3-4x) = -6+20x - 9

2 Answers

7 votes

Answer:

(negative infinity, positive infinity)

Any value of x makes the equation true.

Explanation:

-5(3-4x) = -6+20x - 9

-15 + 20x = -15 + 20x

(negative infinity, positive infinity)

User Sreekanth P
by
5.1k points
4 votes

Answer:

True for all x

Explanation:

-5(3-4x) = -6+20x - 9

Distribute

-15 +20x = -6+20x - 9

Combine like terms

-15 +20x = -15+20x

Subtract 20x from each side

-15 +20x-20x = -15+20x -20x

-15 =-15

This is true for all x

Th

User Lsp
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.